Aortic hemodynamics assessment prior and after valve sparing reconstruction: A patient-specific 4D flow-based FSI model. (August 2021) - Nannini, Guido; Caimi, Alessandro; Palumbo, Maria Chiara; Saitta, Simone; Girardi, Leonard N.; Gaudino, Mario; Roman, Mary J.; Weinsaft, Jonathan W.; Redaelli, Alberto
Abstract: Introduction: Valve-sparing root replacement (VSRR) of the ascending aorta is a life-saving procedure for the treatment of aortic aneurysms, but patients remain at risk for post-operative events involving the downstream native aorta, the mechanism for which is uncertain. It is possible that proximal graft replacement of the ascending aorta induces hemodynamics alterations in the descending aorta, which could trigger adverse events. Herein, we present a fluid-structure interaction (FSI) protocol, based on patient-specific geometry and boundary conditions, to assess impact of proximal aortic grafts on downstream aortic hemodynamics and distensibility. Methods: Cardiac magnetic resonance (CMR), including MRA, cine-CMR and 4D flow sequences, was performed prior and after VSRR on one subject. Central blood pressure was non-invasively acquired at the time of the CMR: data were used to reconstruct the pre- and post-VSRR model and derive patient-specific boundary conditions for the FSI and a computational fluid dynamic (CFD) analysis with the same settings. Results were validated comparing the predicted velocity field against 4D flow dataset, over four landmarks along the aorta, and the predicted distensibility against the cine-CMR derived value. Results: Instantaneous velocity magnitudes extracted from 4D flow and FSI were similar ( p > 0.05), while CFD-predicted velocity was significantly higher ( p < 0.001), especially in the descending aorta of the pre-VSRR model (vmax was 73 cm/s, 76 cm/s and 99 cm/s, respectively). As measured in cine-CMR, FSI predicted an increase in descending aorta distensibility after grafting (i.e., 4.02 to 5.79 10 −3 mmHg −1 ). In the descending aorta, the post-VSRR model showed increased velocity, aortic distensibility, stress and strain and wall shear stress. Conclusions: Our Results indicate that i) the distensibility of the wall cannot be neglected, and hence the FSI method is necessary to obtain reliable results; ii) graft implantation induces alterations in the hemodynamics and biomechanics along the thoracic aorta, that may trigger adverse vessel remodeling. Highlights: Surgical treatment for aortic aneurysm induces hemodynamic alterations. FSI patient-specific modeling to predict hemodynamic alterations after VSRR surgery. Comprehensive comparison of FSI and CFD Results against 4D flow data. FSI approach is more reliable than CFD, that tends to overestimate velocity. Identification of low OSI region where major adverse events may occur.